Tapak Liman (Elephantopus scaber L) As Immunostimulant and Its Effect on Lymphocyte Differentiation in Mice BALB/C - Marmi Kelik (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2015)
Tapak liman (Elephantopus scaber L) is one of the plants that have medicinal properties and has been used for maintenance and improvement of health and disease treatment. The purpose of this study was to determine the effect of extracts of Tapak Liman (Elephantopus scaber L) as immunostimulant to the development of lymphocytes in mice BALB / C. The procedure of this study was to test aqueous extracts in vivo with various treatments (control, treatment of 0.5 g / kg, 1.0 g/ kg, 2.0 g / kg) in healthy mice BALB / C for 2 weeks. After the treatment carried out analysis of the percentage and number of cells that express CD4+, CD8+ and CD4+ CD8 + in thymus organ, using flowcytometry. Analysis of data using one-way ANOVA followed Tukey's test with SPSS. From the analysis showed that the extract of Tapak liman at various doses showed no significant effect on the percentage expression of CD4 + CD8 + and CD4 + CD8 + in thymus organs. While the analysis of the number of cells, extracts of Tapak liman show its effect on the number of cells that express CD4+, CD8 + and CD4 + CD8 + in thymus organs. Concentration of 1.0g / kg of mice showed a good effect on the increase in T helper cells (CD4 +), cytotoxic T cells (CD8 +) and Prothymosit cells (CD4 + CD8 +).